Access Through the Anatomical Snuffbox for Neuroendovascular Procedures: A Single Institution Series. Issue 5 (25th May 2020) - Weinberg, Joshua H; Sweid, Ahmad; Khanna, Omaditya; Mouchtouris, Nikolaos; Asada, Ashlee; Das, Somnath; Curtis, Darcy; Kim, Julie; Romo, Victor; Gooch, Michael Reid; Herial, Nabeel; Tjoumakaris, Stavropoula; et al.
Abstract: BACKGROUND: Distal transradial catheterization in the anatomic snuffbox is an alternate route of access that has started to gain consideration for neuroendovascular procedures. OBJECTIVE: To assess the feasibility and outcomes and present our institution's experience in performing neuroendovascular procedures via distal transradial access (dTRA). METHODS: We conducted a retrospective analysis and identified 120 patients who underwent consecutive neuroendovascular procedures via dTRA in the anatomic snuffbox. Data collection was performed on indication for procedure, sheath size, number of vessels selectively catheterized, fluoroscopy time, procedure duration, radiation exposure, conversion to femoral approach, access site complication, and procedure success. RESULTS: Of 120 patients with an average age of 54.7 yr ± 14.7, 73 (60.8%) underwent diagnostic angiograms, 38 (31.7%) underwent follow-up angiograms, and 9 (7.5%) underwent therapeutic procedures. The overall mean number of vessels catheterized was 2.5 ± 0.1 per procedure, the mean procedure time was 68.3 min ± 43.4, the mean fluoroscopy time was 10.8 min ± 7.6, the mean contrast dose was 70.6 mL ± 39.1, and the mean radiation exposure was 27 672.2 mGycm 2  ± 42 728.4. Successfully completed therapeutic procedures included aneurysm 1 (0.8%), arteriovenous malformation (AVM)/arteriovenous fistula/carotid cavernous fistula 7 (5.8%), and 1 (0.8%) other treatment. Three patients (2.5%) required adjunct transfemoral endovenous access for AVM embolization. Two minor complications (1.67%) were a local wrist hematoma and a radial artery vasospasm without any sequelae. CONCLUSION: Distal radial artery catheterization in the anatomic snuffbox is a safe and effective access site to perform neuroendovascular procedures. Complications and conversion rate are low making it a safe alternative. Graphical Abstract: